Effect of enamel bevel on retention of cervical composite resin restorations: A systematic review and meta-analysis. Issue 7 (July 2015) - Schroeder, Marcos; Reis, Alessandra; Luque-Martinez, Issis; Loguercio, Alessandro Dourado; Masterson, Danielle; Maia, Lucianne Cople
Abstract Objectives To identify if enamel bevelling, compared to no treatment, improves the retention rates and marginal discolouration of cervical composite restorations in non-carious cervical lesions (NCCLs) of adult patients, through a systematic review of the literature and meta-analysis. Sources MEDLINE, Scopus, Web of Science, LILACS, BBO Library, Cochrane Library and SIGLE were searched without restrictions, as well as the abstracts of the annual conference of the IADR and the trials registry. Dissertations and theses were searched using the ProQuest Dissertations and Periódicos Capes Theses databases. Study selection We included randomised clinical trials (RCTs) that compared the retention rates restorations in NCCLs placed with or without bevel with at least 1-year follow-up. The risk of bias tool of the Cochrane Collaboration was used for quality assessment. Data After duplicate removal, 1356 articles were identified. After abstract screening, 14 studies remained and this number was reduced to four after examination of the full-texts. Only two were considered to have a 'low' risk of bias. The overall risk difference was 0.0 (95% CI −0.04 to 0.04) for the retention rate (p = 0.91) and 0.05 (−0.02 to 0.13) for the marginal discolouration (p = 0.17). Conclusions No superiority of bevelled restorations was observed in the short-term follow-up of 1-year, although this conclusion was based on only two RCTs. There is not enough evidence to support the bevelled technique over non-bevelled for NCCLs over longer periods of time. Better standardization and reporting of RCTs of enamel bevelling are necessary in longer-term follow-ups. Clinical significance The literature still lacks a body of evidence to support the benefits of enamel bevel over non-bevelled for longer-term follow-ups, and future randomised clinical trials with low risk of bias should be conducted.